2012
DOI: 10.1111/j.1600-6143.2012.04234.x
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Histology Assessment of Cardiac Allograft Vasculopathy Following Introduction of Everolimus—Results of a Multicenter Trial

Abstract: Clinical trial registry: Clinicaltrials.gov (unique registration number NCT00377962)In this 12-month multicenter Scandinavian study, 78 maintenance heart transplant (HTx) recipients randomized to everolimus with reduced calcineurin inhibitor (CNI) exposure or continued standard CNItherapy underwent matched virtual histology (VH) examination to evaluate morphological progression of cardiac allograft vasculopathy (CAV). Parallel measurement of a range of inflammatory markers was also performed. A similar rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
4
20
0
1
Order By: Relevance
“…Arora et al . [57] compared the morphologic progression of CAV using virtual histology (VH) in patients receiving maintenance immunosuppression with everolimus versus calcineurin inhibitor (CNI). VH analysis revealed a significant increase in calcified and necrotic component among everolimus patients compared to controls.…”
Section: Proliferation Signal Inhibitors (Psi)mentioning
confidence: 99%
“…Arora et al . [57] compared the morphologic progression of CAV using virtual histology (VH) in patients receiving maintenance immunosuppression with everolimus versus calcineurin inhibitor (CNI). VH analysis revealed a significant increase in calcified and necrotic component among everolimus patients compared to controls.…”
Section: Proliferation Signal Inhibitors (Psi)mentioning
confidence: 99%
“…(1). With the use of virtual histology (VH) (2,3), the authors revealed a significant increase in calcified and necrotic tissue component in intimal lesions of the everolimus group of HTx patients compared to controls, while the overall plaque volume was not affected at all.…”
Section: Virtual Histology and The Morphologic Assessment Of Cardiac mentioning
confidence: 98%
“…Dodatkowych informacji dostarczyło wieloośrodkowe badanie, w którym zastosowano IVUS-VH do oceny morfologii i zaawansowania zmian w grupach pacjentów leczonych EVE lub MMF. W okresie powyżej 5 lat od transplantacji serca stwierdzono nasilone wapnienie oraz martwicę, poza tym zwiększone gromadzenie cząsteczek adhezyjnych oraz czynnika von Willebranda u chorych przyjmujących EVE [27]. Obecnie nie jest znany wpływ tych procesów na powikłania odległe i rokowanie CAV.…”
Section: Leczenieunclassified